Study of the Vickers hardness and corrosion behavior of experimental Ti-Mo alloy in dental office bleaching agents - Alves Rezende, Maria Cristina Rosifini; Felipe, Juliana Caires; Nakazato, Roberto Zenhei; Dutra, Conceição Aparecida Matsumoto; Rangel, André Luiz Reis; Limírio, João Pedro Justino de Oliveira; Alves Claro, Ana Paula Rosifini (ARCHIVES OF HEALTH INVESTIGATION, 2017)
At present, titanium and its alloys stand out for their mechanical and biological properties. Vickers hardness and the effect of 15%, 22% and 35% hydrogen peroxide (H2O2) on Ti-10Mo alloy corrosion were evaluated. A conventional double-walled glass cell was used for thermostatization. As reference electrode was used the Ag/AgCl (s)/KClsat and as auxiliary electrode graphite stick. The work electrodes consisted of Ti-10Mo cylinders embedded in polyethylene, with electrical contact by brass wire and silver paint on one end. The electrolyte used was H2O2 in concentrations of 15%, 22% and 35% and potentiodynamic measurements were recorded. The Vickers hardness was evaluated before the treatment using Vickers penetrator under load of 1000g and dwell time of 10s / measurement separately. The results showed an increase in the corrosion values in direct relation with the increase of the H2O2 concentration. At 35% concentration, at constant current of 1.0V the alloy did not passivate, characterizing high corrosion rate. At the concentrations of 15% and 22% the results showed a tendency to pseudopassivation, with release of TiO2 and part of the product of the corrosion becoming semi-adherent to the surface of the working electrode and another part passing through the middle, characterizing intermediate corrosion velocity. It was concluded that higher H2O2concentrations produced higher electrochemical corrosion. Descriptors: Titanium; Alloys; Surface Properties; Corrosion; Tooth Bleaching Agents.